Certain subclasses of starlike and convex functions of complex order - Ravichandran, V.; Bolcal, Metin; Yemişci, Halime Arzu; POLATOĞLU, YAŞAR (My University, 2005)
In the present investigation, we consider certain subclasses of starlike and convex functions of complex order, giving necessary and sufficient conditions for functions to belong to these classes.
Keywords: Starlike functions; Convex functions; Starlike functions of complex order; Convex functions of complex order